Humoral immune response of pregnant goats to two Corynebacterium pseudotuberculosis bacterin formulations - Auad, Jordana (2018)
Caseous lymphadenitis is a chronic suppurative bacterial disease caused by Corynebacterium pseudotuberculosis with a high prevalence in small ruminants. Different vaccine preparations have been employed to control this disease. The adjuvant used in the formulation is a critical factor for the improvement of vaccine efficacy. No commercial vaccines are available in Argentina. The aims of the present work were to compare the specific antibody response against a C. pseudotuberculosis whole cell vaccine formulated with a classical and an immunoestimulant adjuvant in pregnant goats, and to assess the transfer of vaccine- specific antibodies from the goat to the offspring through colostrum. Twenty three pregnant goats were vaccinated. The animals were randomly allocated to three groups: control, aluminum hydroxide Al(OH)3 adjuvant and a new cage-like particle adjuvant (ISPA). Antibodies (IgG) against this antigen were measured by ELISA. A robust humoral immune response was detected in vaccinated animals, with production of specific IgG, without finding significant differences between the vaccines formulated with different adjuvants. High levels of specific antibodies were detected in colostrum samples from both immunized groups, which were passively transfered from goats to offprings. No adverse local reactions in the vaccines injection sites were detected.